Assessment of Molecular Mechanism of Saffron Anti-Stress Property - Babak Arjmand; Mahmood Khodadoost; Mohhamadreza Razzaghi; Mostafa Rezaei Tavirani*; Alireza Ahmadzadeh; Sina Rezaei Tavirani (Iranian Society of Pharmacognosy, 2021)
Background and objectives: There are several documents about protective properties of saffron against stress conditions which refer to the effect of saffron on gene expression pattern of the treated samples.The aim of the present study was determination of the main regulated proteins by saffron extract. Methods: Twenty differentially expressed proteins from a published research were investigated via network analysis and assessed to determine the crucial regulated individuals by Cetoscape software. The network was analyzed by network analyzer application of Cytoscape software, and the central nodes were identified. Results: Twenty queried proteins were included in a network with 9005 nodes and 11446 edges. Analysis of the network revealed that VCP, SOD1, GRP78 (HSPA5), GRP75 (HSPA9), PRDX1, PHB, COMT, and ATP5H are the central proteins which are regulated by saffron extract. Conclusion: Based on the regulated proteins, regulation of mithoconderia and endoplasmic reticulum was identified as the main target of saffron in stress management.